2007
DOI: 10.1016/j.febslet.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Peptide binding proclivities of calcium loaded calbindin‐D28k

Abstract: Calbindin-D28k is known to function as a calciumbuffering protein in the cell. Moreover, recent evidence shows that it also plays a role as a sensor. Using circular dichroism and NMR, we show that calbindin-D28k undergoes significant conformational changes upon binding calcium, whereas only minor changes occur when binding target peptides in its Ca 2+ -loaded state. NMR experiments also identify residues that undergo chemical shift changes as a result of peptide binding. The subsequent use of computational pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…We define 'not directly interacting' as a distance (Ca-Ca) of at least 4.5 Å between residues in calbindin-D28K and the catalytic residues in caspase-3. Lending support to these preliminary studies was that the binding region identified on calbindin-D28K is similar to a region on calbindin-D28K shown previously to be involved in interactions with peptides derived from known targets [11].…”
Section: Computational Dockingsupporting
confidence: 66%
“…We define 'not directly interacting' as a distance (Ca-Ca) of at least 4.5 Å between residues in calbindin-D28K and the catalytic residues in caspase-3. Lending support to these preliminary studies was that the binding region identified on calbindin-D28K is similar to a region on calbindin-D28K shown previously to be involved in interactions with peptides derived from known targets [11].…”
Section: Computational Dockingsupporting
confidence: 66%
“…Here in our present study, we show that of the potential druggable sites within calbindin-D28K, the highest affinity location for the cyclic peptides corresponds to the area where linear peptides have previously been shown to bind (region of EF-hand 2) [8]. This location is immediately adjacent to the site where caspase-3 interacts with calbindin-D28K [10]. We also identify a general consensus sequence of potential cyclic peptide inhibitors of calbindin-D28K.…”
Section: Biochemistry and Pharmacology: Open Accesssupporting
confidence: 58%
“…This study resulted in two high-affinity sites and several lower affinity sites ( Figure 1 and Table 1). The highest affinity site corresponds to the site on calbindin-D28K where a series of linear peptides were previously shown to bind [10]. These linear peptides were derived from the following known calbindin-D28K binding proteins: Ran-binding protein M (RanBPM), myo-inositol monophosphatase (IMPase), and caspase-3/procaspase-3 [7,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations